ASUPAN HARA TERHADAP KUALITAS DAN HASIL KELOPAK BUNGA DAN BIJI ROSELA (Hibiscus sabdarifa) - Suharto Ponco Rahardjo (Caraka Tani: Journal of Sustainable Agriculture, 2009)
Roselle has been popular, because of the calyx become to medicated with high nutrient. The calyx are rich in ascorbic acid and also highly antioxidant. The seed of roselle are high in protein and fatty oil. Therefore the purpose of the research was increased of roselle calyx and seed yield. The research was carried out in Kec. Ngaglik Sleman-Yogyakarta at March-August 2008. The experiment was arranged in factorial, Randomized Complete Block Design, Phospat fertilizer (0, 100, 200 and 300 kg/ha) and Organic liquid fertilizers (0, 1, 2 and 3 cc/l water/plant). Result of the research showed that; 1) the high of the number and dry weight of the roselle calyx at P fertilizer, 200 kg/ha was combined with organic liquid fertilizer 10x2 cc/l water/plant, 2) P fertilizer, 100 kg/ha only was produced high seed yield per plant and high weight of the 1.000 of seed on 200 kg/ha or organic liquid fertilizer 10x2 cc/l water/plant, 3) the high of the Vit. C content of the roselle calyx on organic liquid fertilizer 10x1 cc/l water/plant of P fertilizer, 300 kg/ha only. Roselle has been popular, because of the calyx become to medicated with high nutrient. The calyx are rich in ascorbic acid and also highly antioxidant. The seed of roselle are high in protein and fatty oil. Therefore the purpose of the research was increased of roselle calyx and seed yield. The research was carried out in Kec. Ngaglik Sleman-Yogyakarta at March-August 2008. The experiment was arranged in factorial, Randomized Complete Block Design, Phospat fertilizer (0, 100, 200 and 300 kg/ha) and Organic liquid fertilizers (0, 1, 2 and 3 cc/l water/plant). Result of the research showed that; 1) the high of the number and dry weight of the roselle calyx at P fertilizer, 200 kg/ha was combined with organic liquid fertilizer 10x2 cc/l water/plant, 2) P fertilizer, 100 kg/ha only was produced high seed yield per plant and high weight of the 1.000 of seed on 200 kg/ha or organic liquid fertilizer 10x2 cc/l water/plant, 3) the high of the Vit. C content of the roselle calyx on organic liquid fertilizer 10x1 cc/l water/plant of P fertilizer, 300 kg/ha only.